Risk factors for Australian school-age children in socio-economically disadvantaged populations not passing ear and hearing screening - Catherine M McMahon; Jade McLennan; Neil J Orr; Kai Nash; Phillip Nakad (Sax Institute, 2021)
Objectives and importance of study: The consequences of sensorineural hearing loss in young children include poor speech and language development, poor educational outcomes,and delayed socio-emotional development. For children who face socio-economic disadvantage, middle ear disease is more prevalent, access to primary health care is more difficult, and psychosocial and education supports are limited. Because of this, the consequences may be amplified. Understanding the risks associated with hearing loss and middle ear dysfunction in underserved populations can enable an earlier, more targeted and cost-effective approach to identifying those with hearing loss and effectively connecting them to systems of care. Study type: Retrospective study. Method: This study describes the outcomes of an ear and hearing screening program for children from lower socio-economic backgrounds (n = 2489; mean age 11.0 years, standard deviation 1.74 years) in New South Wales (NSW), Australia, between 2013 and 2016. Screening was conducted in a quiet room, and the test protocol included otoscopy, 226 Hertz (Hz) tympanometry, and pure tone screening at octave frequencies from 500 Hz to 4000 Hz with a referral criterion of 20 decibels hearing level (dB HL) at any one frequency. Outcomes were categorised into 1) pass; 2) middle ear dysfunction only; and 3) did not pass hearing screen (with or without middle ear dysfunction). Multinomial logistic regression was used to investigate risk factors for hearing loss and middle ear dysfunction. The factors examined were age, gender, socio-educational advantage, quarter of year assessed, non-English speaking background (NESB), Aboriginal status and region. Results: Higher risks of middle ear dysfunction were associated with younger age and seasonal variation, with higher risk in winter and spring months (July-September and October-December, compared with January-March). There were no differences between those from NESB and those with English as a first language, between the Aboriginal population and non-Aboriginal population, or between those who resided within or outside a major city. Conclusion: More than one in 10 school-age children from lower socio-economic backgrounds experience hearing loss (11.5%). Targeted ear and hearing screening programs offer an opportunity to identify hearing loss during critical learning years and seasons, mitigating longer-term effects on education, and social and mental health.